PERAN DAN TANTANGAN PENDIDIKAN AGAMA ISLAM DI ERA GLOBAL - Nur Hidayat; Nur Hidayat (Jurnal Pendidikan Agama Islam)
Islam requires his people to be literate and educated people. Expected educated person in today’s global era will be increased, while those who are not educated will be reduced in accordance with present era. Islamic education guides students in their development, both physical and spiritual to form honorable personality and character. And will become moral beings in the future in accordance with the noble values of our nation. Islamic educational purposes according to the Qur’an include (1) describes the position of learners as human beings between God and responsibilities in this life, (2) explaining to do as social beings and responsibilities in order of social life, (3) explain the relationship of man the nature and duty to know the wisdom of creation by way of prosperity of the universe, (4) to explain its relationship with God as the creator of the universe.